Hybrid Real-Time Simulator of Large-Scale Power Systems; IEEE Transactions on Power Systems; Vol. 34, iss. 2 - Andreev M. V. Mikhail Vladimirovich; Gusev A. S. Alexander Sergeevich; Ruban N. Yu. Nikolay Yurievich; Suvorov A. A. Aleksey Aleksandrovich; Ufa R. A. Ruslan Alexandrovich; Askarov A. B. Alisher Bakhramzhonovich; Bems J. Julius; Kralik T. Tomas (2019, 2019)
Title screen